Ethical Decision-making of Health Professionals Caring for People Living with HIV/AIDS in Hunan, China: A Qualitative Study - Xiaoxiao Lu BS; Hangyu Huang MS; Kaveh Khoshnood PhD; Deborah Koniak-Griffin PhD; Honghong Wang PhD; Min Yang PhD (SAGE Publishing, 2022)
Numerous ethical issues surged the moment acquired immunodeficiency syndrome (AIDS) was discovered. As advocates of people living with HIV/AIDS (PLWHA), health professionals encounter many ethical dilemmas in clinical practice. However, it remains unclear how health professionals solve these issues. The descriptive qualitative research was conducted through semi-structured interviews with 22 health professionals from May to August 2018. Three themes emerged from data analyses of the interviews: (1) real ethical dilemma experienced by health professionals, (2) factors influencing ethical judgment, (3) ethical motivations. About two-thirds of participants failed to recall ethical dilemmas experienced in their clinical practice. Emotions, gender, occupation, and difficulty balancing different roles may influence the ethical judgments of health professionals. In the ethical decision-making (EDM) process, most participants took other people's interests into consideration and conformed to law and professional codes of conduct. However, the fear of medical disputes (conflicts with families and others) was experienced by many participants, influencing their ethical behaviors.